Predictors of Anxiety and Depression Symptoms in Indonesian Migrant Workers During Early COVID-19 Pandemic - Liem, Andrian (Universitas Nusa Cendana, 2024)
This study examined anxiety and depression symptoms among Indonesian migrant workers in Macau, Hong Kong, and Taiwan during the early COVID-19 pandemic. An online survey of 491 participants revealed prevalence rates of 31.8% for anxiety symptoms and 26.9% for depression symptoms. Hierarchical logistic regression analysis identified predictors for anxiety symptoms: age, marital status, income, education, and Cantonese fluency. Depression symptoms predictors included age, marital status, and English and Cantonese fluency. Older, married individuals with higher income, education, and language proficiency were less likely to experience anxiety or depression symptoms. These findings contribute to understanding mental health challenges faced by migrant workers during the early pandemic and can inform post-crisis interventions and future public health planning. Stakeholders should consider these results to develop more inclusive strategies for migrant workers in similar situations.